2021
DOI: 10.1007/s00253-021-11199-w
|View full text |Cite
|
Sign up to set email alerts
|

Underground metabolism facilitates the evolution of novel pathways for vitamin B6 biosynthesis

Abstract: The term vitamin B6 is a designation for the vitamers pyridoxal, pyridoxamine, pyridoxine and the respective phosphate esters pyridoxal-5′-phosphate (PLP), pyridoxamine-5′-phosphate and pyridoxine-5′-phosphate. Animals and humans are unable to synthesise vitamin B6. These organisms have to take up vitamin B6 with their diet. Therefore, vitamin B6 is of commercial interest as a food additive and for applications in the pharmaceutical industry. As yet, two naturally occurring routes for de novo synthesis of PLP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…The structure of PLP is shown in the center of the graph. vitamin B 6 biosynthesis (Richts & Commichau, 2021). Although the new vitamin B 6 pathway has to be fully characterized, studies have shown that the underground metabolism in B. subtilis promotes the emergence of a pathway to synthesize necessary cofactors PLP using the novo metabolic pathways Rosenberg et al, 2018).…”
Section: Vitamin B 6 Biosynthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of PLP is shown in the center of the graph. vitamin B 6 biosynthesis (Richts & Commichau, 2021). Although the new vitamin B 6 pathway has to be fully characterized, studies have shown that the underground metabolism in B. subtilis promotes the emergence of a pathway to synthesize necessary cofactors PLP using the novo metabolic pathways Rosenberg et al, 2018).…”
Section: Vitamin B 6 Biosynthesismentioning
confidence: 99%
“…Recently, the underground metabolic pathway for the synthesis of vitamin B 6 has also been discovered. Using suppressor gene analysis of E. coli and B. subtilis carrying the native pathways or heterologous mutations, new pathways for PLP biosynthesis were revealed, including promiscuous enzymes and enzymes already involved in vitamin B 6 biosynthesis (Richts & Commichau, 2021). Although the new vitamin B 6 pathway has to be fully characterized, studies have shown that the underground metabolism in B. subtilis promotes the emergence of a pathway to synthesize necessary cofactors PLP using the novo metabolic pathways (Rosenberg & Commichau, 2019; Rosenberg et al, 2018).…”
Section: Biosynthesis Of Vitamin B6 and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] In this work, the m/z = 232.001 presenting up-regulated in CD patients is concluded to be 4-chloroindoleacetic acid (HMDB0032936, [M+Na] + ), which reflects the abnormal metabolism of tryptophan and probably cause the generation of CD. [29] Moreover, during the serotonin pathway of tryptophan metabolism, 5-hydroxytryptamine (5-HT) is an important gastrointestinal signaling molecule that has been identified as a key metabolic biomarker. [5a, [27][28][29] And the m/z = 259.105 may belong to 5-hydroxytryptophan(5-HTP, HMDB0004185, [M+H] + ) which is the producer of the 5-HT.…”
Section: Analysis Of Serum Metabolic Fingerprints For CD Diagnosis By Machine Learningmentioning
confidence: 99%
“…[29] Moreover, during the serotonin pathway of tryptophan metabolism, 5-hydroxytryptamine (5-HT) is an important gastrointestinal signaling molecule that has been identified as a key metabolic biomarker. [5a, [27][28][29] And the m/z = 259.105 may belong to 5-hydroxytryptophan(5-HTP, HMDB0004185, [M+H] + ) which is the producer of the 5-HT. The over-expression of 5-HTP in patients in this work possibly causes the dysbiosis of the gut microbiota, finally leading to the occurrence of CD.…”
Section: Analysis Of Serum Metabolic Fingerprints For CD Diagnosis By...mentioning
confidence: 99%